The Arabidopsis Golgi-localized GDP-L-fucose transporter is required for plant development - Carsten Rautengarten (Nature Portfolio, 2016)
Nucleotide sugars are transported from the cytoplasm to the Golgi lumen where they are incorporated into cell wall polysaccharides and used for glycosylation of proteins and lipids. Here the authors identify GFT1, an ArabidopsisGolgi-localized GDP-fucose transporter that is required for plant growth and development